ROLE OF GENETIC INTERACTIONS IN THE INHERITANCE OF GRAIN PROTEIN, TRYPTOPHAN AND LYSINE PERCENTAGE IN MAIZE (ZEA MAYS L.) UNDER CONTRASTING WATER REGIMES - M. Hussain; T. T. Kiani; A. Ghafoor; G. Qadir (Journal of Animal and Plant Sciences, 2016)
Maize is top most produced cereal and serves millions of people as their staple food globally. It is important source of nutrients like starch, protein and oil contents. However, normal maize varieties are deficient in essential amino acids of tryptophan and lysine. Understanding of genetic effects controlling the expression of these traits is important for development of maize varieties with favourable balances of protein and essential amino acids. In this study, generation mean analysis was used to understand the genetic effects responsible for these traits in different environmental conditions. Ten crosses and their subsequent generations F1, F2, back-cross 1 (BC1) and back-cross 2 (BC2) were developed and evaluated for genetic effects under normal irrigation supply and water stress conditions. Results of Hayman’s six parameter model showed that additive effects, dominance effects and epistatic interactions played role in the inheritance of these traits. The significance of these genetic effects and interactions varied for different parental combinations under different water regimes. Thus, the information provided by this study can guide breeders to design specific strategies for particular parental combinations, aiming to improve protein, tryptophan and lysine percentages.
Keywords: generation mean analysis; Hayman’s six parameter model; genetic effects; protein percentage; maize